GelMA-Encapsulated hDPSCs and HUVECs for Dental Pulp Regeneration. (February 2017) - Khayat, A.; Monteiro, N.; Smith, E.E.; Pagni, S.; Zhang, W.; Khademhosseini, A.; Yelick, P.C.
Pulpal revascularization is commonly used in the dental clinic to obtain apical closure of immature permanent teeth with thin dentinal walls. Although sometimes successful, stimulating bleeding from the periapical area of the tooth can be challenging and in turn may deleteriously affect tooth root maturation. Our objective here was to define reliable methods to regenerate pulp-like tissues in tooth root segments (RSs). G1 RSs were injected with human dental pulp stem cells (hDPSCs) and human umbilical vein endothelial cells (HUVECs) encapsulated in 5% gelatin methacrylate (GelMA) hydrogel. G2 RSs injected with acellular GelMA alone, and G3 empty RSs were used as controls. White mineral trioxide aggregate was used to seal one end of the tooth root segment, while the other was left open. Samples were cultured in vitro in osteogenic media (OM) for 13 d and then implanted subcutaneously in nude rats for 4 and 8 wk. At least 5 sample replicates were used for each experimental group. Analyses of harvested samples found that robust pulp-like tissues formed in G1, GelMA encapsulated hDPSC/HUVEC-filled RSs, and less cellularized host cell–derived pulp-like tissue was observed in the G2 acellular GelMA and G3 empty RS groups. Of importance, only the G1, hDPSC/HUVEC-encapsulated GelMA constructs formed pulp cells that attached to the inner dentin surface of the RS and infiltrated into the dentin tubules. Immunofluorescent (IF) histochemical analysis showed that GelMA supported hDPSC/HUVEC cell attachment and proliferation and also provided attachment for infiltrating host cells. Human cell-seeded GelMA hydrogels promoted the establishment of well-organized neovasculature formation. In contrast, acellular GelMA and empty RS constructs supported the formation of less organized host-derived vasculature formation. Together, these results identify GelMA hydrogel combined with hDPSC/HUVECs as a promising new clinically relevant pulpal revascularization treatment to regenerate human dental pulp tissues.